Exploring bacteria-surface interactions - Carabelli, Alessandro M. (2019)
Bacteria adhere to almost any surface. Medical-device biofilm-centred infections pose an enormous threat, particularly from multi-antibiotic resistant pathogens. Biofilm formation is largely understood and encompasses an initial,reversible bacterial cell surface-attachment phase followed by irreversible surface-attachment, leading to the formation of biofilms that can be up to 1,000 times more resistant to antibiotics and refractory to host immune defences. A better understanding of bacterial-surface interactions should aid human intervention into this process to reduce biofilm formation on implanted medical devices.